2019
DOI: 10.1186/s12984-019-0553-5
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted gait training for balance and lower extremity function in patients with infratentorial stroke: a single-blinded randomized controlled trial

Abstract: Background Balance impairments are common in patients with infratentorial stroke. Although robot-assisted gait training (RAGT) exerts positive effects on balance among patients with stroke, it remains unclear whether such training is superior to conventional physical therapy (CPT). Therefore, we aimed to investigate the effects of RAGT combined with CPT and compared them with the effects of CPT only on balance and lower extremity function among survivors of infratentorial stroke. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 51 publications
6
55
0
Order By: Relevance
“…According to previous studies evaluating the effect of RAGT as an add-on to conventional physiotherapy, patients with (subacute or chronic) stroke exhibited improved ambulation function, lower-extremity motor function, balance, and gait performance both immediately postintervention and at follow-up, and these improvements were superior to those conventional physiotherapy [14,16,17,19,21,22,24,25,33]. By contrast, some studies have shown that training effects in locomotion function, activities of daily living, and gait were not superior to those of conventional stroke training in patients with subacute stroke [15,18,20,23].…”
Section: Discussionmentioning
confidence: 96%
“…According to previous studies evaluating the effect of RAGT as an add-on to conventional physiotherapy, patients with (subacute or chronic) stroke exhibited improved ambulation function, lower-extremity motor function, balance, and gait performance both immediately postintervention and at follow-up, and these improvements were superior to those conventional physiotherapy [14,16,17,19,21,22,24,25,33]. By contrast, some studies have shown that training effects in locomotion function, activities of daily living, and gait were not superior to those of conventional stroke training in patients with subacute stroke [15,18,20,23].…”
Section: Discussionmentioning
confidence: 96%
“…The results gave information that combined training could improve the activities of life (ADLs) and quality of life (QoL) of patients, compared with the other two groups. In an experiment that was carried out to explore the effect of RAGT on balance and lower limb function of survivors of off infratentorial stroke [23], it was clear that RAGT could improve standing balance function and lower limb motor function for patients with infratentorial stroke more effectively, compared with routine rehabilitation training in the same period of time.…”
Section: Discussmentioning
confidence: 99%
“…In recent years, studies recommending the use of exoskeletons in gait training for stroke patients are emerging (Tefertiller et al, 2011;Mehrholz and Pohl, 2012;Pennycott et al, 2012). Parallelly, clinical trials also show the therapeutic benefits of exoskeletons in balance and locomotion (Yeung et al, 2018;Kim et al, 2019;Ii et al, 2020;Moucheboeuf et al, 2020). For example, The ReWalk (ReWalk Robotics, Israel) provides targeted assistance of both paretic ankle plantarflexion and dorsiflexion in overground walking for patients with stroke (Awad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%